2019
DOI: 10.1080/1331677x.2019.1699139
|View full text |Cite
|
Sign up to set email alerts
|

Intangible capital and business productivity

Abstract: The importance of intangible capital as a driver of productivity growth is recognised at both macroeconomic and microeconomic levels. However, in general, there is a lack of strong empirical evidence in the relevant literature on the connection between micro and macro approaches. This study integrates both perspectives to analyse how internal and external intangible capital influence the productivity of companies and, therefore, economic growth. A model is estimated in which the total factor productivity of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
8
0
2
Order By: Relevance
“…It is elicited that the rising level of non-financial enterprise financialization significantly lowers down total factor productivity of enterprises, and furthermore, the decrease in productivity mainly arises from technical innovation investments that are “crowded out” by non-financial enterprise financialization. This finding basically matches up with viewpoints proposed by Bellocchi et al (2020), Stockhammer (2004), and Campling (2020), Aalbers (2008), Lashitew (2017), and Rico and Cabrer-Borras (2020). As for those conclusions in some studies contained in literature documents regarding micro enterprise financialization, they appear contradictory with the conclusion in this paper, for they indicate that the increase in corporate productivity could stem from corporate investments in R&D, innovation and real business that are stimulated by corporate allocation of financial assets for the purpose of great returns and alleviated financing constraints (Akbar et al, 2017; Mannasoo et al, 2018; Nasir et al, 2021; Thomas et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is elicited that the rising level of non-financial enterprise financialization significantly lowers down total factor productivity of enterprises, and furthermore, the decrease in productivity mainly arises from technical innovation investments that are “crowded out” by non-financial enterprise financialization. This finding basically matches up with viewpoints proposed by Bellocchi et al (2020), Stockhammer (2004), and Campling (2020), Aalbers (2008), Lashitew (2017), and Rico and Cabrer-Borras (2020). As for those conclusions in some studies contained in literature documents regarding micro enterprise financialization, they appear contradictory with the conclusion in this paper, for they indicate that the increase in corporate productivity could stem from corporate investments in R&D, innovation and real business that are stimulated by corporate allocation of financial assets for the purpose of great returns and alleviated financing constraints (Akbar et al, 2017; Mannasoo et al, 2018; Nasir et al, 2021; Thomas et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…As for adverse viewpoints, enterprise financialization obviously imposes the “crowding-out” effect upon enterprises’ investment in main businesses and innovation (Stockhammer, 2004), while the decreasing funds for real investment and R&D greatly lowers down enterprises’ capabilities of innovation (Nguyen et al, 2020). Consequently, the development of enterprises in main businesses will be impaired (Aalbers, 2008), and the improvement in total factor productivity of enterprises will be held back (Bellocchi et al, 2020; Rico & Cabrer-Borras, 2020).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…In general, it has been observed that rationality, in its pursuit of efficiency, has been accompanied by a gradual dehumanization of organizations (Ritzer, 2005) which threatens employees' sense of identity and their relationships with others (Gill, 2019). On the other hand, it has been found that internal and external intangible capital influences the productivity of companies and, therefore, economic growth (Rico & Cabrer-Borr as, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the influence of age composition and human capital on TFP, Ji and Lai (2015) found that improving human capital allocation efficiency is the best way to TFP growth. Paz and Bernard ı (2020) thought that intangible capital (human capital) has a positive effect on companies' productivity as well as a spillover effect. Ilmakunnas et al (2004) used matching data on Finnish manufacturing enterprises and workers to examine the impact of workers' personal characteristics on labour productivity.…”
Section: Literature Reviewmentioning
confidence: 99%